SISTEM INFORMASI AKUNTANSI PENJUALAN BERBASIS WATERFALL MODEL UNTUK PERUSAHAAN DAGANG - Sri Harjunawati (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Profit-oriented companies always try to get the maximum difference in sales above the cost. Use of Information Systems Sales accounting that is integrated and follows technological developments will be able to increase sales volume while creating efficiency. In trading companies, especially trading companies with cash sales systems, the watterfall model with the Unified Modeling Language (UML) as a system tool can be used to develop the sales system becomes a sales system that integrates with the inventory system so that there will be a synchronization between the quantity and price of goods owned by the company and the number of goods needed by the customer. In terms of marketing, speed and the accuracy of information is a separate service that can create customer loyalty. The application is very helpful in the company's Internal Control System.